First description of the male of Yaobinthrips yangtzei (Thysanoptera: Thripidae) - Li, Yajin; Xie, Yong-Hui; Zhang, Hongrui (Zootaxa, 2016)
The monobasic Thripinae genus Yaobinthrips has been known only from females, and the objective here is to provide a description of the male. A member of the Frankliniella genus-group, the type species, yangtzei Zhang et al. (2010) was described from specimens taken in Sichuan Province of Southwestern China from the flowers of Dalbergia yunnanensis [Fabaceae]. In April, 2015 a sample of both sexes of this thrips species was taken from the white flowers of the same plant species, but in Yunnan Province. This plant is actually widespread in southwestern China in Yunnan, Sichuan, Guizhou Provinces and Guangxi Zhuang Autonomous Region. Provinces, growing at an elevation ranging from 1400 to 2200 meters, and flowering from April to May (Li et al. 2007).